CRAFTING HIZBIYYIN IN CONTEMPORARY INDONESIA: Da’wah and Recruitment of Hizbut Tahrir Indonesia in South Sulawesi (State Islamic University (UIN) of Sunan Ampel Surabaya, 2011)
This article aims at analysing the growing membership of Hizbut Tahrir Indonesia (HTI) by looking at its local development in Makassar, South Sulawesi. While many scholars have emphasized external factors in explaining the rise of Islamist movements, including HTI, this study emphasizes internal explanation from the movement itself. It discusses the strong relationship between HTI da’wah doctrines, recruitment strategy and the joining process. The various recruitment methods and strategies of HTI are in line with its doctrinal stages of da’wah, namely the stage of culturing (tathqif), the stage of interaction with the ummah, and the stage of taking over the government. This article suggests that individual persuasion through pre-existing interpersonal networks is crucial in attracting young Muslims to participate in HTI. Borrowing theories of conversion by Lofland-Stark and Wiktorowicz, the article demonstrates three processses of joining in HTI: cognitive opening, religious seeking, and socialization.